Truthful but Misleading: Advanced Linguistic Strategies for Lying Among Children - Hu, Chao; Huang, Jinhao; Wang, Qiandong; Weare, Ethan; Fu, Genyue (Frontiers in Psychology, 2020)
We explored whether children could apply linguistic strategies for lying, i.e., manipulating linguistic content of speech to mislead others. We announced a knowledge-test entailing prizes in the classrooms of a primary school and a middle school. Altogether 79 Chinese children (6-18 years) voluntarily participated in the test: listening to a series of animal sounds before guessing the names of the animals. Meanwhile, behind the participants, a video was playing images that ostensibly corresponded to the sounds being played. In fact, this was not necessarily the case, i.e., some items cannot be solved because the sounds played are not from any animal but machine-synthesized. Participants were instructed not to look back at the video. However, 51 children peeked at the video for the unsolvable items, although the peeking behavior decreased with age. Moreover, when explaining how they correctly guessed the unsolvable items, children as young as six years old were able to apply a linguistic strategy (i.e., "capability attribution") for lying. Besides "capability attribution", Children also applied "fortune attribution" and "topic shift" for lying. Finally, "fortune attribution" and "topic shift" increased with age. Therefore, educators need to be aware that children are able to apply verbal strategies for lying that could involve truthful statements (i.e., "topic shift") or statements that are difficult to be proved as untruthful (i.e., "fortune attribution").